Peningkatan Motivasi Kerja Pada PT. APM Armada Suspension - Dhahlil Ridhwan Allaudin; Enjang Suherman (CV. ITTC INDONESIA, 2024)
The aim of this research is to increase the work motivation of PT employees. APM vehicle suspension. Descriptive research methods are used to describe behavioral characteristics and work environment conditions that influence employee motivation. Data was collected through observation, interviews and document analysis to gain an in-depth understanding of motivation and hygiene factors that influence employee performance. The research results show that factors such as salary, benefits, physical working conditions, interpersonal relationships, company practices and job security greatly influence motivation. an employee's work. In addition, the implementation of motivation programs such as incentives, career development and increasing job opportunities has proven to be effective in increasing employee motivation and performance. The research conclusion is that a stimulating work environment, a fair compensation system, career opportunities and competitive salaries and incentives are important to improve employee motivation. Recommendations given include increasing employment opportunities, implementing reward programs and improving communication between management and employees to create a more conducive work environment.